Pengembangan mobile learning berbasis android untuk meningkatkan hasil belajar kognitif siswa pada pembelajaran IPS - Utomo, Eko Prasetyo (Jurnal Teori dan Praksis Pembelajaran IPS, 2021)
This study aimed to develop android-based mobile learning and to find out its effectiveness in improving student cognitive learning outcomes in social studies learning. The development process refers to the model of Dick et al. The results of the development are in the form of android-based mobile learning with the main components, namely: 1) introduction to subjects; 2) subject competence; 3) material; and 4) practice questions in the form of quizzes. The feasibility level of the social studies material test is 89.91 percent very feasible category and learning media test is 89.42 percent very feasible category. Sequentially the feasibility level for individual trials was 77.78 percent in the feasible category, the small group trial was 77.92 percent in the feasible category, and the field trial was 83.43 percent for the very feasible category. The product effectiveness test using the t-test showed mobile use. Android-based learning can improve student cognitive learning outcomes in social studies subjects. The media developed has been tested and can be tested on a wider range of subjects for product perfection. DOI: http://dx.doi.org/10.17977/um022v6i12021p45